How can the Thai Foundation Garment Industry compete successfully in International Supply Networks? - Ngamdumrongkiat, Sumate (2012)
The apparel industry is a significant income source for developing countries. Thailand is one of the largest textile and garment industries in South East Asia (Lotharukpong, nd) and it is the second most important industrial segment regarding to employment (SourceAsean.com, 2010). From the interviewing with TGMA, Thai Foundation garment industry is one of world-class industries in Asia and has potentially grown in the future. After the quota liberation in 2005, Thai foundation garment industry has been facing many challenges recently, which including the hyper competition from other developing countries, the EU and the US economic downturn, the rise in labour minimum wage in April 2012, the devastated floods in 2011 and many other external factors. It is important to aware of the upcoming AEC (ASEAN Economic Community) in 2015 and also the Wear American Act of 2012.